The Bork-Baykal Phenomenon in Congenital Melanocytic Nevus - Tugba Kevser Ustunbas Uzuncakmak; Defne Ozkoca; Server Serdaroglu (Dermatology Practical & Conceptual, 2021)
The Bork-Baykal phenomenon is a new entity that was first reported in large congenital melanocytic nevus 2015 and classified as a specific variant of congenital melanocytic nevus (CMN). Afterward, this rare feature was reported in other skin disorders reflecting the different embryologic developmental periods of the nipple-areola complex (NAC) with the surrounding skin. Preserving of the NAC appears to bowl over the clinicians both in congenital and acquired skin disorders.